KONTRIBUSI PERSEPSI PEMUDA-PEMUDI TENTANG PELAYANAN PENGAJARAN DAN KEBAKTIAN PEMUDA-PEMUDI TERHADAP PERTUMBUHAN IMAN PEMUDA-PEMUDI GEREJA JEMAAT ALLAH INDONESIA (GJAI) SEKTOR VI - Sitepu, Elisabeth; Ginting, Eka Hosana (JURNAL PENDIDIKAN RELIGIUS; Vol 2 No 2 (2020): JULI, 2020)
This study aims at determining the Contribution of Youth Perceptions About Teaching Services and Youth Services to the Growth of Youth Faith of Indonesian Church of God (GJAI) Sector VI. The study was conducted using the ex post facto method. The population of the study is 120 people, the determination of the number of research samples was based on Irawan Soehartono's theory. Then the sample of this study is 25% of the population size that is 30 respondents, and tested it to 30 respondents, with each item's variable items is 30 items. This questionnaire has been tested for validity and reliability, meaning that only the questionnaire passes the results of the trial used to capture data. The data analysis technique used to test the research hypothesis is the parametric statistical t-test. The use of this statistic is based on fulfilling the parametric analysis requirements test, where the research data is normally distributed and there are significant contributions. The results show that, Teaching Services (X 1 ) are in the Good Category that is 56.6%. Youth Conventions include the Fairly Good category of 43.3%. and the Youth Faith Growth of the Church of Indonesia Church of God (GJAI) Sector VI is included in the Good Category , which is 43.3%. The acquisition of normality data variables X and Y at a significant level of 5% is X 2 count < X 2 table so: Understanding Teaching Services (X 1 ), X 2 count = 2.035 <X 2 table = 11.07, Youth-Youth Service X 2 count = 2.126 < X 2 table = 11.07 and Growth of Youth Faith- Indonesian Church of God Youth Church (GJAI) Sector VI X 2 count = 4,445 < X 2 table = 11.07 so that the research data is normally distributed. From the results of the above research is recommended to every Youth Church of Indonesian Church of God Community (GJAI) Sector VI has an understanding of Teaching Services, and it will be better if parents guide them well and appropriately, so that they have a good Growth of Youth Faith in the Church of Indonesia Church of God (GJAI) Sector VI in their lives.